Ex Vivo - Growth Response of Porcine Small Intestinal Bacterial Communities to Pharmacological Doses of Dietary Zinc Oxide - Starke, Ingo C. (Public Library of Science, 2013)
Piglets were fed diets containing 57 (low) or 2425 (high) mg zinc from analytical grade zinc oxide (ZnO) ·kg(−1) feed. Digesta samples from the stomach and jejuna of 32, 39, 46 and 53 d old animals (n  = 6 per group) were incubated in media containing 80, 40, 20 and 0 µg·mL(−1) soluble zinc from ZnO. Turbidity was recorded for 16 h and growth parameters were calculated. Additionally, DNA extracts of selected samples were analyzed via qPCR for different bacterial groups. Samples from animals fed the low dietary zinc concentration always showed highest rate of growth and lowest lag times in media without added zinc. However, media supplemented with zinc displayed highest growth rates and lowest lag time in the high dietary zinc group. Specific growth rates and lag time showed significant differences on day 32 and 39 of age, but rarely on days 46 and 53 of age. Bacterial growth in digesta samples from the high dietary zinc group was less influenced by zinc and recovered growth more rapidly than in the low dietary zinc group. Specific growth rates and bacterial cell numbers from qPCR results showed that lactobacilli were most susceptible to zinc, while bifidobacteria, enterobacteria and enterococci exhibited increased growth rates in samples of animals from the high dietary zinc treatment. No treatment related differences were observed for clostridial cluster IV and the Bacteroides-Prevotella-Porphyromonas cluster. The diversity of enterobacteria after incubation was always higher in the high dietary zinc treatment or in medium supplemented with 80 µg·mL(−1) soluble ZnO. This study has shown that a pharmacological dosage of ZnO leads to a reduced ex vivo- bacterial growth rate of bacteria from the stomach and jejunum of weaned piglets. In view of the rapid bacterial adaptation to dietary zinc, the administration of ZnO in feeds for weaned piglets might only be beneficial in a short period after weaning.